Changes in Medicaid Physician Fees and Patterns of Ambulatory Care - Sandra L. Decker (SAGE Publishing, 2009)
Controlling for state fixed effects and other factors, this paper estimates the effect of the generosity of Medicaid physician payment levels on the volume and site of ambulatory care received by Medicaid patients compared to privately insured patients. Results indicate that cuts in Medicaid physician fees lead to statistically significant reductions in the number of visits for Medicaid patients compared to privately insured patients. Cuts in fees also lead to a statistically significant shift away from physician offices and toward hospital emergency departments and especially outpatient departments. Primary diagnoses for which site of care shifts are most pronounced include hypertension, asthma, urinary tract infections, and diabetes.